The effect of the keto diet on lipid profile with type two diabetic patients - Fadwa Ghassan; Ateka Mohammed; Zainab Kazim (Разработка и регистрация лекарственных средств)
Introduction. In the developed world, among the main causes of disease and death is type 2 diabetes. It is a significant public health issue with rising prevalence, with more than 380 million patients estimated to be affected by 2025.Aim. To evaluate the effect of ketogenic diets on glycemic control in patients with type II DM in Kirkuk and Mosul provinces.Materials and methods. Patients with T2DM in both Mosul and Kirkuk cities were enrolled in this study to evaluate the effect of keto diet on HbA1c level and Lipid profile variations between 1/9/2022 to 1/4/2023.Results and discussion. This study shows that the distributions of patients according to age and gender there was about 43.3 % female and 56.7 % male and the age variations, female with age above 56 years old was 30 % while male 60.7 %. A significant p value was shown in HbA1C variations before and after keto diet (0.0001), also in lipid profile of a significant p value before and after keto diet (0.001) regarding total Glyceride a significant p value highly was (0.002). Due to the large particle size of LDL-C, it has been hypothesized that this elevation in LDL-C would not likely cause cardiovascular problems. For individuals with type 2 diabetes, the low-calorie-ketogenic VLCK diet (<50 g of carbohydrates per day) is a safe, well-tolerated, and recognized medical nutritional therapy option when used in conjunction with an interventional weight loss program that offers support for lifestyle and behavioral modification over a 4-month period.Conclusion. Diabetic and ketogenic diet there is a good clear relationship regarding the HbA1c and lipid profile. Further studies are required for larger numbers of patients and longer duration follow up.